(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2023)
This article attempts to demonstrate that in Enrique Lihn’s poetic selected corpus the subject of enunciation travels the itinerary established by modern poetry by virtue of which there is an access to the polysemic origin of language and finally to the semantic whitening that mortal nothingness confers (Blanchot). This journey is motivated by a romantic heartbreaking experience that leads the speaker to death where he obtains the secret of poetry as a decoded language. This decoding generates a non-being, an initially precarious subject and exiled from himself, who is later empowered by the materiality of his language. A thanatological language that re-enters life through poetic discourse and resemanticizes the afterlife under the perspective of an intravital death (Jankélévitch).